Highlighting type A RRs as potential regulators of the dkHK1 multi-step phosphorelay pathway in Populus. (December 2018) - Chefdor, F.; Héricourt, F.; Koudounas, K.; Carqueijeiro, I.; Courdavault, V.; Mascagni, F.; Bertheau, L.; Larcher, M.; Depierreux, C.; Lamblin, F.; Racchi, M.L.; Carpin, S.
Highlights: Isolation of ten type A RRs from poplar clone 'Dorskamp'. Nucleocytoplasmic and nuclear localization for eight and two of them respectively. Eight type A dkRRs could interfere the dkHK1a-b/dkHPts/dkRRB MSP. Abstract: In previous studies, we highlighted a multistep phosphorelay (MSP) system in poplars composed of two hybrid-type Histidine aspartate Kinases, dkHK1a and dkHK1b, which interact with three Histidine Phosphotransfer proteins, dkHPt2, 7, and 9, which in turn interact with six type B Response Regulators. These interactions correspond to the dkHK1a-b/dkHPts/dkRRBs MSP. This MSP is putatively involved in an osmosensing pathway, as dkHK1a-b are orthologous to the Arabidopsis osmosensor AHK1, and able to complement a mutant yeast deleted for its osmosensors. Since type A RRs have been characterized as negative regulators in cytokinin MSP signaling due to their interaction with HPt proteins, we decided in this study to characterize poplar type A RRs and their implication in the MSP. For a global view of this MSP, we isolated 10 poplar type A RR cDNAs, and determined their subcellular localization to check the in silico prediction experimentally. For most of them, the in planta subcellular localization was as predicted, except for three RRAs, for which this experimental approach gave a more precise localization. Interaction studies using yeast two-hybrid and in planta BiFC assays, together with transcript expression analysis in poplar organs led to eight dkRRAs being singled out as partners which could interfere the dkHK1a-b/dkHPts/dkRRBs MSP identified in previous studies. Consequently, the results obtained in this study now provide an exhaustive view of dkHK1a-b partners belonging to a poplar MSP.